Comparison of polarized vs other types of endurance training intensity distribution on cardiorespiratory function - Oliveira, P. S. (University of Porto, 2023)
Polarized Training (POL) has been recently suggested to be superior to other training intensity distributions (TIDs) regimens for improving endurance performance. The first aim of this thesis was to systematically review and meta analyze the evidence comparing POL to other TIDs on surrogates of cardiorespiratory function. PubMed, Scopus, and Web of Science were searched for studies with more than or equal to four weeks duration comparing POL with other TID exercise interventions assessing either VO2max/peak, time-trial, time to exhaustion or velocity or power at the second ventilatory or lactate threshold. Eighteen studies met the inclusion criteria (n = 449 subjects). The pooled effect estimates suggest that POL is superior to other TIDs for improving VO2max/peak. This superiority, however, only occurs in shorter duration interventions (<12 weeks) and for the case of moderately/well trained subjects. All the remaining cardiorespiratory function surrogates analyzed were similarly affected by POL compared to other TIDs.